Assessing Feasibility and Safety of Using Ultrasonic Bone Aspirator for Revision Endoscopic Sinus Surgery - Joo Yeon Kim; Jung Ho Oh; Seo Bin Kim; Jae Hwan Kwon (Journal of Rhinology, 2022)
Background and Objectives This study introduced and evaluated the efficacy of an ultrasonic bony aspirator (UBA) in revision endoscopic sinus surgery and compared the outcomes to those of the traditional cold instrument approach. Methods This retrospective study enrolled 57 patients who underwent revision endoscopic sinus surgery between June 2010 and December 2017, 17 patients with a UBA approach and 40 patients with traditional instruments. Results Median Lund–Kennedy scores showed a statistically significant difference between the two groups at 3 months (p=0.004). Synechiae occurred in 17.6% and 35% of cases in the UBA and traditional groups, respectively. The mean operative time was significantly shorter in the traditional group (p=0.001). Conclusion The use of a UBA in revision endoscopic sinus surgery was safe and effective.